Is vigorous physical activity effective for preventing kidney stones? - Wang, Yuanfu; Wei, Qing; Dai, Yue; Chen, Sisi; Cheng, Bo (Frontiers in Public Health, 2025)
BackgroundWith a high rate of occurrence and recurrence, kidney stones represent a common urological issue that poses a substantial burden on public health infrastructures globally. While prior research has linked poor diet and lifestyle to a heightened susceptibility to kidney stones, the impact of daily vigorous physical activity (VPA) duration on kidney stone incidence remains under-investigated.Materials and methodsUtilizing data from the NHANES database covering the years 2007 to 2020, this study undertakes a large-scale cross-sectional analysis of adults with full records of daily VPA and kidney stone history. Daily VPA time was calculated by summing the VPA duration (in minutes) from typical work and recreational activities. To analyze the association between VPA time and kidney stone prevalence, logistic regression was used, with a focus on potential non-linear relationships. A piecewise linear model estimated threshold effects, accompanied by subgroup and interaction analyses.ResultsOf the 12,128 participants in this analysis, 1,021 (8.41%) had previously experienced kidney stones. Findings indicated a positive correlation between the duration of daily VPA and kidney stone prevalence. In the analysis of VPA time divided into quartiles, the highest quartile exhibited a 1.49-fold increase in kidney stone prevalence vs. the lowest quartile (OR = 1.49, 95% CI: 1.21–1.83, P for trend < 0.001). A smoothing curve fit showed a significant non-linear relationship between VPA time and kidney stones prevalence (P for non-linearity = 0.0007). Piecewise linear regression indicated a VPA threshold of 240 min, after which kidney stone prevalence increased by 0.3% for each additional minute of daily VPA (OR = 1.003, 95% CI: 1.000–1.006), up to 360 min, at which point the prevalence plateaued.ConclusionThis study suggests that VPA is associated with an increased risk of kidney stones, as longer daily VPA duration corresponds to a higher prevalence of kidney stones. This increase in prevalence may be related to the higher urine specific gravity caused by prolonged VPA. To strengthen these findings, future prospective cohort studies are recommended.